Peningkatan Kemampuan Berkomunikasi Peserta didik Melalui Layanan Bimbingan Kelompok Teknik Permainan pada Peserta didik Kelas Xii Bdp 1 Semester 1 Tahun Pelajaran 2020/2021 - Anggraeny, Dahlia (Cakrawala: Jurnal Pendidikan, 2022)
The ability to communicate learners who tend to be low makes teachers interested in knowing how to improve the ability to communicate learners, especially in class XII BDP 1. The formulation of research problems how to organize group guidance with game techniques can increase the ability to communicate learners. The study carried out 2 actions, each cycle of 4 meetings. Study subjects of students of Class XII BDP 1 SMK Negeri 1 Dukuhturi Semester 1 of The 2020/2021 School Year. There was an increase in learners' communication skills from 82.05% before using group guidance services to 94.9% after using game techniques